2001
DOI: 10.1093/glycob/11.12.1035
|View full text |Cite
|
Sign up to set email alerts
|

KM+, a lectin from Artocarpus integrifolia, induces IL-12 p40 production by macrophages and switches from type 2 to type 1 cell-mediated immunity against Leishmania major antigens, resulting in BALB/c mice resistance to infection

Abstract: The outcome and severity of some diseases correlate with the dominance of either the T helper 1 (Th1) or Th2 immune response, which is stimulated by IL-12 or IL-4, respectively. In the present study we demonstrate that gamma interferon (IFN-gamma) secretion by murine spleen cells stimulated with KM(+), a mannose-binding lectin from Artocarpus integrifolia, is due to IL-12 induction, because (1) macrophages from several sources (including cell lines) produced IL-12 p40 in response to KM(+), and (2) lectin-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 25 publications
5
79
0
8
Order By: Relevance
“…In the present study, IL-12 and IFN-γ were expressed in the lesion, which is in agreement with the findings of other authors who had shown that these 2 cytokines are important for the development of protective immune responses in experimental leishmaniasis (Panunto-Castelo et al, 2001;Hernández et al, 2006). The ample expression of iNOS by immunized animals suggests that there was production of nitric oxide (NO) in the lesion, leading us to believe that the NO, together with IL-12 and TNF-α, acts in an important and synergistic way in mediation of the local inflammatory process.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, IL-12 and IFN-γ were expressed in the lesion, which is in agreement with the findings of other authors who had shown that these 2 cytokines are important for the development of protective immune responses in experimental leishmaniasis (Panunto-Castelo et al, 2001;Hernández et al, 2006). The ample expression of iNOS by immunized animals suggests that there was production of nitric oxide (NO) in the lesion, leading us to believe that the NO, together with IL-12 and TNF-α, acts in an important and synergistic way in mediation of the local inflammatory process.…”
Section: Discussionsupporting
confidence: 93%
“…The lectins are widely distributed in nature in seeds, leaves, barks, bulbs, rhizomes, roots, cotyledon and tubers depending on the plant species. Lectins, such as the ConBr from Canavalia braziliensis and KM+ from Artocarpus integrifolia induce IFN-γ and IL-12 p40 production and promote an inversion of the Th2 to Th1 cytokine pattern in BALB/c mice infected with L. amazonensis and L. major, respectively (Barral-Netto et al, 1996;Panunto-Castelo et al, 2001). Saponins, such as from Quillaja spp, Quillaja saponaria, and the conformational isomers of QuilA sapogenin, have been shown to increase the cutaneous response to Leishmania antigens and enhance serum levels of IFN-γ, and may protect against murine infections with L. major, L. donovani and Leishmania chagasi Palatnik de Sousa et al, 2004;Oliveira-Freitas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…7). The addition of anti-IL-12 mAb to mannose-binding lectin-treated macrophage cultures restored the induction of IL-4 and inhibited the induction of IFN-␥ synthesis by T cells (41). In contrast, p43 had no effect on the production of IL-4 in lymph node cells (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have reported that lymphocytes and natural killer (NK) cells can produce IFNγ with anti-tumor activity (45). Although ArtinM had previously been demonstrated in murine models of infection to stimulate IFNγ expression (13,15,17), the present study is the first to detect a significant increase in mRNA expression of IFNγ in response to ArtinM treatment during hepatocarcinogenesis. Increased IFNγ expression was accompanied by a reduction of preneoplastic foci.…”
Section: Graphic Representations Of the Effects Of Artinm On P53 (A)mentioning
confidence: 47%
“…ArtinM is a d-mannose-binding lectin found in the seeds of Artocarpus heterophyllus that interacts with N-glycans and is associated with receptors on the surface of phagocytic cells to induce production of inflammatory mediators, such as tumor necrosis factor alpha (TNFα) (13), interleukin 12 (IL12) and interferon gamma (IFNγ) (14). Moreover, the protective effect of ArtinM against intracellular pathogens (15,16,17) and against the development of hematopoietic cancer (18) is well-known. However, it is necessary to investigate the effects of ArtinM against neoplastic progression in vivo.…”
mentioning
confidence: 99%